Record of the occurrence of Lachesis muta (Serpentes, Viperidae) in an Atlantic Forest fragment in Paraíba, Brazil, with comments on the species’ preservation status - Ricardo Rodrigues; Ralph Albuquerque; Diego Santana; Daniel Orsi Laranjeiras; Arielson Protázio; Frederico Gustavo Rodrigues França; Daniel Mesquita (Biotemas)
In this study, one describes a new record of the bushmaster snake, Lachesis muta, in an Atlantic Forest fragment in the state of Paraíba, northeastern Brazil. This species is regarded as the largest venomous snake from the New World. The specimen was found at night, crossing a narrow shortcut, close to a slope, about 20m away from a waterfall. The occurrence of L. muta in this fragment demonstrates the importance of conservating Atlantic Forest fragments for preservating this species.